2017
DOI: 10.1111/tmi.13019
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus dynamics in body fluids and risk of sexual transmission in a non‐endemic area

Abstract: Abstractobjective To understand Zika virus (ZIKV) dynamics in fluids of infected individuals and the risk of sexual transmission.methods Prospective study at two centres in Spain. Patients with probable or confirmed diagnosis of ZIKV infection were clinically followed up, and fluid samples were collected from saliva, serum, urine and semen or vaginal secretion following the study protocol. Non-traveller-sexual partners were offered to participate.results From January 2016 to December 2016, we included a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…The majority of the studies evaluated ZIKV shedding in FGT of non-pregnant women using lower genital tract samples (LGT) 21,25,[35][36][37][44][45][46][47][48] . Very few samples from the upper genital tract (UGT) have been studied 42,49 (Table 1).…”
Section: Zikv Kinetics In Fgt Of Non-pregnant Womenmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the studies evaluated ZIKV shedding in FGT of non-pregnant women using lower genital tract samples (LGT) 21,25,[35][36][37][44][45][46][47][48] . Very few samples from the upper genital tract (UGT) have been studied 42,49 (Table 1).…”
Section: Zikv Kinetics In Fgt Of Non-pregnant Womenmentioning
confidence: 99%
“…Subsequently, some studies have reported the presence and persistence of ZIKV RNA in the vaginal and/or cervical samples of non-pregnant women 21,25,36,37,[44][45][46][47][48] . In these studies, the authors reported data on the symptoms, and the variability on the period of viral RNA detection and persistence in vaginal and/or cervical samples.…”
Section: Zikv Kinetics In Fgt Of Non-pregnant Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…No other arboviruses are thought to be transmitted sexually, and the transmission can occur before, during, or after the onset of symptoms and from asymptomatic patients. 2,3 The first major reported outbreaks of ZIKV infection were described in French Polynesia in 2013 and 2015. At that time, some neurologic disabilities in infants of infected pregnant women were observed; however, the maternal-fetal transmission was not suspected at that time.…”
mentioning
confidence: 99%